2015
DOI: 10.1039/c5ra15333f
|View full text |Cite
|
Sign up to set email alerts
|

Labile dioxy-functionalised zwitterionic imidazolinium salt: access to zwitterionic and neutral imidazolidin-2-ylidene derivatives and π-acceptor properties of imidazolidine-2-selones

Abstract: The synthesis of the title compound and effect of backbone oxy-derivatisation in imidazolidine derivatives on the π-acceptor property are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“… Known strategies (A and B) and new strategy developed in this study (C) to access 4(5)‐heteroatom‐functionalized imidazol(in)ium salts. In the known strategies, typical reagents containing preinstalled heteroatomic substituents include: i ) bielectrophiles such as α‐halogenoacetic [13a,c, 18a–e] or propiolic acid derivatives, [18f,g] α‐halogenated ketones, [18h] derivatives of oxalic acid, [18i,j] and 1,2‐dihalogen(or diphosphonio)‐1,2‐diaminoethenes; [13a, 18k] ii ) binucleophiles such as (thio)amides of aminoacetic acid; [18l,m] and iii ) oxazolinium salts [18n] …”
Section: Introductionmentioning
confidence: 99%
“… Known strategies (A and B) and new strategy developed in this study (C) to access 4(5)‐heteroatom‐functionalized imidazol(in)ium salts. In the known strategies, typical reagents containing preinstalled heteroatomic substituents include: i ) bielectrophiles such as α‐halogenoacetic [13a,c, 18a–e] or propiolic acid derivatives, [18f,g] α‐halogenated ketones, [18h] derivatives of oxalic acid, [18i,j] and 1,2‐dihalogen(or diphosphonio)‐1,2‐diaminoethenes; [13a, 18k] ii ) binucleophiles such as (thio)amides of aminoacetic acid; [18l,m] and iii ) oxazolinium salts [18n] …”
Section: Introductionmentioning
confidence: 99%
“…One of the recently suggested and introduced modifications of carbenes is the addition of a positive or negative charge to NHCs. Anionic NHCs (Figure a) were obtained both in the isolated form and in metal complexes, and in the latter systems, they were shown to possess, in general, good stability because of their high affinity for transition metals bearing a formal positive charge . Surprisingly, however, there is not a single example of any of the anionic NHC derivatives complexing Ru to form a potential metathesis catalyst, although such systems have been proposed in computational studies and predicted to be stable and good candidates for efficient metathesis catalysts. , The cationic NHCs (Figure b) were also reported, and it was shown that the positive charge on the NHC affects the electron properties by reducing the σ-donation properties and slightly increasing the π-acidity.…”
Section: Introductionmentioning
confidence: 99%